2017
DOI: 10.1002/cncr.30549
|View full text |Cite
|
Sign up to set email alerts
|

Improving access to high‐cost cancer drugs in Latin America: Much to be done

Abstract: Lack of access to high-cost medications is a complex issue at the intersection of economics, medicine, politics, and ethics, and it poses a significant threat to global health care. The problem is even more significant in low- and middle-income countries, such as those in Latin America, where governments and individuals struggle to pay for products that are priced at several times the level of their per capita gross domestic product. In this review, we examine the determinants for increasing drug costs and how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 60 publications
(125 reference statements)
0
58
0
6
Order By: Relevance
“…Even though molecular biomarkers (ie, gene expression, signaling pathways, and protein expression) and immunological factors (ie, neutrophil/lymphocyte ratio, immune infiltrate [Immunoscore®]) may be useful in guiding treatment decisions, epidemiological studies have demonstrated that patient demographics and “classic” clinicopathological characteristics may also be important predictors of outcomes among patients with CC . In addition, while genetic‐based targeted cancer therapy is emerging, histological tumor subtyping is more readily available in the vast majority of clinical settings . In turn, many patients may benefit from personalized treatment based on the histological tumor subtyping .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though molecular biomarkers (ie, gene expression, signaling pathways, and protein expression) and immunological factors (ie, neutrophil/lymphocyte ratio, immune infiltrate [Immunoscore®]) may be useful in guiding treatment decisions, epidemiological studies have demonstrated that patient demographics and “classic” clinicopathological characteristics may also be important predictors of outcomes among patients with CC . In addition, while genetic‐based targeted cancer therapy is emerging, histological tumor subtyping is more readily available in the vast majority of clinical settings . In turn, many patients may benefit from personalized treatment based on the histological tumor subtyping .…”
Section: Discussionmentioning
confidence: 99%
“…21 In addition, while genetic-based targeted cancer therapy is emerging, histological tumor subtyping is more readily available in the vast majority of clinical settings. [24][25][26][27] In turn, many patients may benefit from personalized treatment based on the histological tumor subtyping. [28][29][30][31] In particular, several authors have reported that histological tumor subtype may be a reliable hallmark of the underlying genetic tumor characteristics and, in turn, have a role in predicting prognosis.…”
Section: Propensity Score Matching Analysesmentioning
confidence: 99%
“…The American Cancer Society predicts that the worldwide weight of malignancy will increase to 21.7 million crisp cases by the year 2030 [24,28]. According to a report circulated by iMShealth Institute for Healthcare Informatics in June 2016, the worldwide market for tumor medications developed to a record level of US$107 billion out of 2015, and is relied upon to achieve US$150 billion by 2020 [29]. It is surveyed that one out of eight deaths is the eventual outcome of disease, and almost 70% of all tumor deaths occur in low and centre salary nations.…”
Section: Causes Of Cancermentioning
confidence: 99%
“…57,1820 Latin America and the Caribbean accounts for 9% of the global population and 8.5% of global expenditure on health, whereas Europe, Canada, and the United States (US) collectively represent approximately 18% of the world’s population but account for about 75% of world health expenditures. 21 Healthcare systems across Latin America are heterogeneous, fragmented, and segregated, with diverse, independent health-coverage schemes.…”
Section: Introductionmentioning
confidence: 99%
“…8 With health a constitutional right across much of the region, patients without private health insurance may have to resort to legal action against the government in order to access standard therapies. 20,2426 Additionally, several biologics are reported to have higher prices in some Latin American countries than in the European Union (EU). 27 The availability of biosimilars of the most widely utilized biologics could play an important part in addressing such challenges.…”
Section: Introductionmentioning
confidence: 99%